Two new Neotropical species of the Dasyhelea mutabilis group (Culicomorpha: Ceratopogonidae) - Díaz, Florentina; Felippe-Bauer, Maria Luiza; Spinelli, Gustavo Ricardo (Papéis Avulsos de Zoologia, 2017)
Two new species of Dasyhelea Kieffer, Dasyhelea jorgei Diaz, Felippe-Bauer & Spinelli sp. nov. and Dasyhelea mineira Diaz, Felippe-Bauer & Spinelli sp. nov. are described, illustrated and photographed from Peru and Brazil respectively, based on male and female adults. These species are typical members of mutabilis species group and are compared with similar species within the group.